Modeling the effect of bullet velocity and composite fiber orientation on the ballistic impact strength of Eglass/isophthalic polyester composites - Fahmi, Fariz Rifqi Zul; Hermawan, Harry; Hanggara, Fuad Dwi (Jurnal Polimesin, 2024)
Numerical simulation has been widely used as a cost-effective and practical solution to understand phenomena previously determined only through experiment. One example is ballistic impact simulation using the finite element method. The simulation of ballistic impact was used to determine the effect of fiber orientation and bullet velocity on the ballistic impact strength of E-glass/isophthalic polyester. The analysis and simulation process were conducted using ANSYS Workbench v19.2 software. The simulation involved firing a 9 mm FMJ Parabellum bullet with a mass of 6.98 grams at a composite panel measuring 100×100×0.57 mm with 12 layers at specified velocities. This study varied fiber orientation ([±45°] and [0°, 90°]) and bullet velocities (300, 500, and 800 m/s), using symmetrical laminate arrangements. The simulation results showed that the E-glass/isophthalic polyester composite with a fiber orientation of [±45°] has 16.51% higher ballistic strength compared to the [0°, 90°] fiber orientation. The highest ballistic impact strength for the [±45°] fiber orientation occured at 500 m/s, surpassing the 300 m/s and 800 m/s velocities by 12.92% and 43.81%, respectively. The Wen model was used for the validation process, and the error values between the computed and modeling results for the E-glass/isophthalic polyester composite ranged between 1.62% and 20.64%.Isophthalic polyester, E-glass, composite laminate, explicit dynamic, ballistic impact.